N-doping effects on the oxygen sensing of TiO2 films - Buono, Camila (2017)
Gas sensors based on Titanium dioxide films have been a subject of interest due to its high sensitivity and low cost. The sensing mechanism of this type of sensors is based on the conduction mechanism, which is governed by the potential barriers formed at the inter-grains of the polycrystalline structure. The shape of these potential barriers strongly depends on the characteristics of the material, and then it is expected that a doping aggregation will affect significantly the conductivity and thus the sensitivity of the sensor. In this work, we study the effect in the oxygen sensitivity of titanium dioxide films due to N-doping. We developed a model in order to explain our experimental results based on the fact that, for the particle size of our titanium dioxide samples, grains are completely depleted of carriers.